Space-time unified coordinate coding model for digital twin cities - Huangchuang Zhang; Ge Li (Big Earth Data)
The data of the digital twin city is voluminous and diverse, with the characteristics of massive, multi-dimensional, real-time, and unstructured. Therefore, how to realize data integration and efficient management is crucial to the value release of the twin system. Based on this, this paper starts from the most basic temporal and spatial attributes of data, and researches the spatio-temporal unified coordinate coding model for digital twin city, in order to support the unified aggregation and association of all kinds of related data, and realize the spatio-temporalization of data, the spatio-temporalization of model and the spatio-temporalization of scene. Inspired by the GeoSOT theoretical system, this paper designs a spatio-temporal unified coordinate coding model with binary bit operation as the core, and constructs the corresponding spatio-temporal grid model. Finally, the correctness and efficiency of the method in this paper are verified by model coding and decoding experiments, query experiments and visualization experiments. The model is expected to provide a basic spatio-temporal guidance framework for spatio-temporal data integration of digital twin cities.